Social context matters: Ethnicity, discrimination and stress reactivity. (September 2017) - Busse, David; Yim, Ilona S.; Campos, Belinda
Highlights: Latino ethnicity predicts heightened cortisol reactivity through discrimination. This mediational effect is moderated by sex, with significant findings only in males. Latino ethnicity is not directly associated with heightened cortisol reactivity. Abstract: Exposure to chronic discrimination is associated with increased morbidity and mortality. The study of biobehavioral pathways linking discrimination with health outcomes has mostly focused on the cardiovascular system, with fewer studies addressing the hypothalamus-pituitary-adrenal (HPA) axis. In this study we tested associations between Latino ethnicity, experiences of discrimination, and cortisol responses to an acute laboratory stressor. One hundred fifty eight individuals (92 female, 66 male) between the ages of 18 and 29 years participated in the study. Salivary cortisol was measured once before and eight times after administration of a laboratory stressor (the Trier Social Stress Test). Past experiences of discrimination were measured with the Experiences of Discrimination Scale. Findings from conditional process modeling suggest that Latino ethnicity predicted a) heightened cortisol reactivity and b) more pronounced cortisol recovery through discrimination experiences (mediator), and that this effect was further moderated by sex with a significant indirect effect only among males. The direct path from Latino ethnicity to cortisol reactivity or cortisol recovery was, however, not significant. In sum, findings suggest that Latino ethnicity and discrimination interact to predict cortisol dysregulation, which implies that an appropriate model for understanding minority health discrepancies must incorporate interactive processes and cannot simply rely on the effects of ethnicity or discrimination alone.